2021
DOI: 10.3390/su132212517
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Personality and Creative Performance: Mediating Roles of Creative Self-Efficacy and Moderated Mediation Role of Psychological Safety

Abstract: Previous research has suggested that employees’ proactive personality can enhance their creative performance. However, studies that address the underlying mechanism of the effect of proactive personality on creative performance have been scarce. Additionally, contextual factors that could serve as useful conditions have received insufficient academic attention. Therefore, the present study proposed that creative self-efficacy serves as a mediator and psychological safety serves as a moderator in the positive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…A mediating role of self-efficacy on the relationship between BAS and sports success was fully confirmed in this study, consistent with hypothesis H4 and a previous study [ 2 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. According to the RST [ 32 , 33 , 34 ], an approach and avoidance motivated behavior results from the interaction between neuropsychological personality traits and motivational stimuli that possess a specific value (more or less attractive).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A mediating role of self-efficacy on the relationship between BAS and sports success was fully confirmed in this study, consistent with hypothesis H4 and a previous study [ 2 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. According to the RST [ 32 , 33 , 34 ], an approach and avoidance motivated behavior results from the interaction between neuropsychological personality traits and motivational stimuli that possess a specific value (more or less attractive).…”
Section: Discussionsupporting
confidence: 92%
“…Self-efficacy was found as a mediator in the relationships between the Big-Five personality traits and academic performance [ 50 , 51 ] and between a proactive personality and creative performance [ 52 ] and between goal setting and performance in the context of human resource management [ 53 ]. Furthermore, Sherman et al [ 49 ] found the mediating effect of flossing self-efficacy on the relationship between BIS/BAS motivational system, flossing intention, and health-related flossing behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the correlational analysis in Table 1, there was a positive correlation between proactive personality and creativity, which is consistent with the findings of Mediation model linking proactive personality and creativity through growth mindset, fixed mindset and golden mean thinking. previous research (Zhao and Gao, 2014;Kong and Li, 2018;Choi et al, 2021). When acquiring the third language, L3 learners are always curious about and interested in diverse cultures all over the world.…”
Section: Proactive Personality and Creativity In Chinese Third Langua...mentioning
confidence: 99%
“… 24 Based on social information processing theory, leadership safety commitment, an important source of social information, fully conveys the appreciation and trust of leadership to the miners, inspiring psychological gratitude and safety on the part of the miners. 25 This means that when senior management attaches importance to the safety culture of an enterprise and begins to attend to the safety production of the miners, the miners perceive this, which enhances their psychological safety. In addition, leadership safety commitment, as one of the important indicators of enterprise safety culture, is very helpful to improve the safety atmosphere of enterprises.…”
Section: Theoretical Basis and Hypothesesmentioning
confidence: 99%